The Concept of Opposition According to the Fundamentalists and its Applications to the Chapter on (the Covering of the Worshipper) from the Book (Bulugh al-Maram min Adillat al-Ahkam) by al-Hafiz IbnHajar al-Asqalani (d. 852 AH) (Islamic Sciences Journal, 2025)
ABSTRACTThis research aims to understand the true concept of opposition among the scholars of the principles of jurisprudence (usul al-fiqh), by clarifying its meaning and related aspects, and examining the scholars' opinions on it through their quotations.Research methodology: Inductive-deductive.Among the most important findings of the research are:1-The concept of opposition is one of the important terminological topics in the science of the principles of jurisprudence (usul al-fiqh).2-The concept of opposition has several types.3- The validity of the concept of opposition is disputed, but it is generally accepted as evidence by the majority of scholars of the principles of jurisprudence (usul al-fiqh).
Keywords: Al-Asqalani , fundamentalists, reaching the goal, the prayer cover, Violation